Reproductive Regulation and Oxidative Stress Alleviation of Chinese Herbal Medicine Therapy in Ovariectomised Mouse Model. (7th July 2019) - Wu, Chung-Hsin; Wang, Sheue-Er; Hsu, Chih-Hsiang; Hsu, Yu-Tsen; Lu, Chen-Wen; Chuang, Wu-Chang; Lee, Ming-Chung
Abstract : In Taiwan, the herbal formula B401 is considered as a health supplement for middle-aged women that can alleviate sweating, anxiety, and sleep disorders. However, the relevant mechanisms are still unclear. In this study, we evaluated the beneficial effects of the herbal formula B401 therapy in the reproductive regulation of ovariectomised mice. Female ICR mice were randomised into four groups: wild-type (WT) mice with sham treatment, wild-type mice treated with the herbal formula B401, bilateral ovariectomised (OVX) mice with sham treatment, and bilateral ovariectomised mice treated with the herbal formula B401. Mice were orally given the herbal formula B401 at a dose of 30 mg/kg bw/day for 2 weeks. At the end of oral treatment with sham or the herbal formula B401, levels of reactive oxygen species (ROS), calcium, phosphorus, and estradiol-17 β in the blood; uterine weight and endometrial thickness; and expressions of estrogen receptor α (ER α ), estrogen receptor β (ER β ), progesterone receptor (PR), vascular endothelial growth factor (VEGF), and superoxide dismutase 2 (SOD2) in the uterine tissue were examined and then compared among the four groups of mice. We found that OVX mice decreased levels of calcium, phosphorus, and estradiol-17 β in the blood, decreased uterine weight and endometrial thickness, and decreased expressions of ER α, ER β, PR, and SOD2 in the uterine tissue but increased blood ROS levels compared with those of WT mice. In addition, OVX mice with the herbal formula B401 therapy can increase levels of calcium, phosphorus, and estradiol-17 β in the blood, increase uterine weight and endometrial thickness, and increase expressions of ER α, ER β, PR, VEGF, and SOD2 in the uterine tissue but decrease blood ROS levels. Our results may provide reasonable explanation for the reproductive regulation of the herbal formula B401 therapy.